Analisis Pengaruh Orientasi Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan Pada PT Matahari Departemen Store Metropolitan Mall Bekasi - Umar Usman; Nurlaela (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2022)
PT Matahari Department Store Metropolitan Mal Bekasi began to experience a decline in sales. This can be seen from the company's declining sales in recent years. Employee turnover is also a number of important reasons why there has been a decline in employee performance, because some of these new employees have not been able to fully absorb the company profile and the products that must be sold to the market. It seems that the work orientation program for new employees needs refreshment or even further job training for new employees so that the company's stability does not decrease with the entry of new employees. The purpose of this study is to find out how much influence work orientation and work motivation have on increasing employee performance at PT Matahari Department Store Metropolitan Mal Bekasi. From the results of multiple linear regression analysis, the regression equation Y = 6.214 + 0.611X1 + 0.262X2 is obtained. From this equation it can be interpreted that orientation and motivation can run optimally, then and improve employee performance at PT Matahari Department Store Metropolitan Mal Bekasi.